Improved performance of bimetallic oxides CuO–Y2O3 synthesized by sol–gel for methanol steam reforming. Issue 11 (7th July 2022) - Shen, Qiuwan; Cai, Zhongwen; Shao, Zicheng; Yang, Guogang; Li, Shian
Abstract: A series of bimetallic oxide catalysts CuO–Y2 O3 were synthesized by different sol–gel methods for methanol steam reforming (MSR). The performance of the synthesized catalyst was investigated by characterization of X‐ray diffraction, Brunauer–Emmett–Teller, scanning electron microscopy, transmission electron microscope, and X‐ray photoelectron spectrometer techniques. The effects of different complexing agents on the property of the CuO–Y2 O3 were identified. The results showed that CuO–Y2 O3 synthesized by citric acid‐EDTA as a complexing agent showed the best performance, which has the largest specific surface area and shows the highest dispersion of particles and lowest average size than others. The relatively large specific surface area could increase the contact area between the catalyst and the feed, thereby improving the catalytic performance of the catalyst. Moreover, without hydrogen reduction treatment, the selectivity of hydrogen to CuO–Y2 O3 can reach more than 99%, whereas the selectivity of CO is only 0.3% (under the reaction conditions: temperature of 300°C, the ratio of water to methanol of 4:1, feed flow rate of 4 ml/h). The addition of yttrium enhances the interaction of the two active components, copper and yttrium, thereby preventing the migration of the active components. This work provides a potential and economical Cu–Y oxide catalyst for onboard in situ hydrogen production from MSR, because it can reduce the hydrogen reduction process time.